If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(f + 5) + -4(f + -3) = 0 Reorder the terms: 5(5 + f) + -4(f + -3) = 0 (5 * 5 + f * 5) + -4(f + -3) = 0 (25 + 5f) + -4(f + -3) = 0 Reorder the terms: 25 + 5f + -4(-3 + f) = 0 25 + 5f + (-3 * -4 + f * -4) = 0 25 + 5f + (12 + -4f) = 0 Reorder the terms: 25 + 12 + 5f + -4f = 0 Combine like terms: 25 + 12 = 37 37 + 5f + -4f = 0 Combine like terms: 5f + -4f = 1f 37 + 1f = 0 Solving 37 + 1f = 0 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-37' to each side of the equation. 37 + -37 + 1f = 0 + -37 Combine like terms: 37 + -37 = 0 0 + 1f = 0 + -37 1f = 0 + -37 Combine like terms: 0 + -37 = -37 1f = -37 Divide each side by '1'. f = -37 Simplifying f = -37
| m/8=120 | | 7(x+3)+5=5(x-6)+x-4+x | | m^2=-3m+40 | | 2[0]+4[y]=16 | | 6(4y+7)=-29 | | 6x^2=-51.75 | | -0.3(-0.6-2x)=1.1x | | x-3/5x=8 | | 5u^2-9u+4=0 | | 2[2]+4[y]=16 | | 1/1-10i | | 2[-2]+4[y]=16 | | 3a-6a+12=30 | | 90=4x+6 | | X(7x+8)=2x^2-21x+42 | | 3-2m=-(3m-5) | | 4(6+9v)=-29 | | 3.18n=31.8 | | 8/9-2-9 | | -4[2]+2[y]=12 | | 11n=99 | | 372817279732+790-2919203= | | 17+x(15+10)+18+11x= | | -10m+36=2(-m+2) | | 14m=210 | | -4[0]+2[y]=12 | | -(x-7)2= | | -4[-2]+2[y]=12 | | x-9=8(2x+13)-18 | | -8(1-9f)=-33 | | 5x=6x+60 | | 3(x-8)+(-6x)=-3(x-9)+6 |